Supply chain analysis of agricultural and plantation commodities in North Maluku, Indonesia - AJAM, M. RIDHA; RASULU, HAMIDIN; ASHARI, REYNA; TRIDTITANAKIAT, PAVALEE CHOMPOORAT; MURTINI, ERNI SOFIA; JABID, ABDULLAH W.; KAMALUDDIN, ABDUL KADIR; NURJANNAH, SITI; FATMAWATI, MILA; ROZAKI, ZUHUD; ABDULLAH, HAYUN (Smujo International, 2026)
Abstract. Ajam MR, Rasulu H, Ashari R, Tridtitanakiat PC, Murtini ES, Jabid AW, Kamaluddin AK, Nurjannah S, Fatmawati M, Rozaki Z, Abdullah H. 2026. Supply chain analysis of agricultural and plantation commodities in North Maluku, Indonesia. Asian J Agric 10 (1): g100122. https://doi.org/10.13057/asianjagric/g100122. North Maluku is an archipelagic province in eastern Indonesia where agricultural and plantation supply chains are shaped by dispersed geography and reliance on maritime transport. This study applied a qualitative approach, combining in-depth interviews and field observation. Thirty informants were purposively selected, consisting of 15 farmers, 5 intermediaries, and 10 local traders engaged in agricultural distribution. The research examined supply chain structures, transport modes, and logistical constraints across seven major islands-Hiri, Halmahera, Bacan, Obi, Morotai, Sula, and Taliabu. The results identified five distinct supply chain typologies. Types 1-3 are associated with local vegetable distribution and short intra-island flows from farmers to end consumers, local retailers, or collectors. Type 4 reflects inter-island trade networks, commonly used for locally abundant fruits and for imported products such as carrots, potatoes, and garlic. Type 5 is for the plantation crops, such as nutmeg, cloves, and coconuts, which are largely export-oriented and involve the longest chain with multiple intermediaries. Across all types, profitability is strongly influenced by transport costs and weather-dependent marine disruptions, affecting both the availability and price stability of agricultural products as essential commodities. To enhance food security and reduce dependency on external sources, there is a need to strengthen local agricultural production through crop diversification, infrastructure development, and targeted farmer support initiatives. The results provide insights into how archipelagic geography shapes agricultural supply chains and point to strategies for building more resilient and equitable food systems.